"Give me actual music stuff!": The nature of feedback in a collegiate songwriting class. (July 2019) - Hill, Stuart Chapman
This study aimed to understand the nature of feedback that students and teacher exchanged in a workshop-based collegiate songwriting course. Two research questions guided the study: (1) What kinds of feedback do students and teacher give as they respond to each other's work? and (2) What factors contribute to the culture of feedback in this class? Data sources included field notes from class observations, individual interviews with four informant students, a group interview, and a student-conducted interview of the investigator, who was also the instructor of the class. The analysis generated four themes that describe the feedback culture of this songwriting class: micro feedback, macro feedback, feedback roles, and overall feedback culture. Recommendations for practice and future research are presented.